Evaluating and Analyzing the Tourism Brand Position of Fars Province Based on the Identity of National Competitiveness - Barat Ali Khakpour; Hamed abbasi; nemat shakarami (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2018)
Considering the global competitive environment, branding tourism potential is important in directing resources and attracting investment. Today, most countries and cities are planning to earn foreign exchange using this green industry. Therefore, in this research, considering the high potential of Fars province in the field of historical tourism, we seek to evaluate the tourism brand of Fars province based on the tourism development document of this province in 1404 and national competitiveness. In terms of the methodology, this is a descriptive-analytical and in terms of the purposes, this is an applied research. The required data and information collected using library and documentary sources (tourism development document of Fars province) and survey method (questionnaire-interview). The results show that Fars province in terms of tourist attraction and branding criteria, has a competitive map below Mashhad with 3.5 points and 3 out of 5 points, respectively, and it is in a competitive situation with Isfahan province and above other national and regional rivals (Khuzestan, Yazd, and Kerman). The result of the proportional map shows that the main factors influencing the development and branding of tourism in Fars province are macro-management of the country, lack of credit, political perspectives on the historical tourism of Fars province, restrictions of the Islamic society and international sanctions. Also, the most important features of Fars province which have four characteristics of rarity, non-repeatable, irrelevant and valuable are Shah Cheragh shrine, the tomb of the characters and national monuments, historical monuments of Fars province. Therefore, considering these sources and the significant variables affecting tourism branding in Fars province, a map of strategic alignment has been drawn and appropriate strategies have been suggested